The Use of Kahoot Application in Learning Mufrodat Surah Al-Fatihah for Ninth Grade Students of Cerdas Murni Tembung Junior High School - Hasibuan, Anastasya; Zainuddin, Darwin (Universitas Ahmad Dahlan, 2024)
In today's digital era, learning apps are increasingly important in education. One interesting application is Kahoot, a game-based learning platform. Surah Al-Fatihah is an important part of religious learning, especially Arabic, which is often the focus of the teaching process. This study aims to determine the impact of using the Kahoot application in learning mufrodat Surah Al-Fatihah on class IX students of Cerdas Murni Tembung Private Junior High School. This research uses a qualitative descriptive method with a case study design that focuses on 1 class consisting of 29 students. The sample was selected using purposive sampling technique. Data were collected through observation, interviews and documentation analysis. The results showed that the use of Kahoot application has a positive impact in learning Arabic, especially in helping students understand the mufrodat contained in Surah Al-Fatihah and increasing students' interest in learning. The implication of this finding is the importance of considering the utilization of digital tools to add an interesting learning experience for students in learning Arabic mufrodat. This study is expected to provide a foundation for further research on the use of Kahoot application in the context of learning Arabic mufrodat contained in other surahs in the Qur'an.